Block‐adaptive quantum mechanics: An adaptive divide‐and‐conquer approach to interactive quantum chemistry. Issue 6 (29th October 2012) - Bosson, Maël; Grudinin, Sergei; Redon, Stephane
Abstract We present a novel Block‐Adaptive Quantum Mechanics (BAQM) approach to interactive quantum chemistry. Although quantum chemistry models are known to be computationally demanding, we achieve interactive rates by focusing computational resources on the most active parts of the system. BAQM is based on a divide‐and‐conquer technique and constrains some nucleus positions and some electronic degrees of freedom on the fly to simplify the simulation. As a result, each time step may be performed significantly faster, which in turn may accelerate attraction to the neighboring local minima. By applying our approach to the nonself‐consistent Atom Superposition and Electron Delocalization Molecular Orbital theory, we demonstrate interactive rates and efficient virtual prototyping for systems containing more than a thousand of atoms on a standard desktop computer. © 2012 Wiley Periodicals, Inc.